Organizational Methodological Aspects of Accounting for the Execution of the State Budget and State Targeted Funds - Eshqobilov Akhmad Javliyeevich (International Journal of Formal Education, 2025)
The state budget is a centralized fund of state funds (including funds of state target funds), which provides for sources of income and the amount of receipts from them, as well as the directions and amount of expenditure of funds allocated for specific purposes during the financial year. The structure of the state budget of the Republic of Uzbekistan includes the budget of the Republic, the budget of the Republic of Karakalpakstan and local budgets. In the process of budget execution, budget revenues are formed in the prescribed manner and expenditures are carried out according to the budget classification. This article discusses the process of budget execution, information about the organization and maintenance of budget accounting.